Inhibition of Protein Farnesylation Arrests Adipogenesis and Affects PPARγ Expression and Activation in Differentiating Mesenchymal Stem Cells - Daniel Rivas; Rahima Akter; Gustavo Duque (PPAR Research)
Protein farnesylation is required for the activation of multiple proteins involved in cell differentiation and function. In white adipose tissue protein, farnesylation has shown to be essential for the successful differentiation of preadipocytes into adipocytes. We hypothesize that protein farnesylation is required for PPARγ2 expression and activation, and therefore for the differentiation of human mesenchymal stem cells (MSCs) into adipocytes. MSCs were plated and induced to differentiate into adipocytes for three weeks. Differentiating cells were treated with either an inhibitor of farnesylation (FTI-277) or vehicle alone. The effect of inhibition of farnesylation in differentiating adipocytes was determined by oil red O staining. Cell survival was quantified using MTS Formazan. Additionally, nuclear extracts were obtained and prelamin A, chaperon protein HDJ-2, PPARγ, and SREBP-1 were determined by western blot. Finally, DNA binding PPARγ activity was determined using an ELISA-based PPARγ activation quantification method. Treatment with an inhibitor of farnesylation (FTI-277) arrests adipogenesis without affecting cell survival. This effect was concomitant with lower levels of PPARγ expression and activity. Finally, accumulation of prelamin A induced an increased proportion of mature SREBP-1 which is known to affect PPARγ activity. In summary, inhibition of protein farnesylation arrests the adipogenic differentiation of MSCs and affects PPARγ expression and activity.